Reference management training at the postgraduate program of State Islamic Institute of Samarinda - Hasiara, La Ode; Suyudi, Muhammad; Sailawati, Sailawati (Community Empowerment, 2021)
The purpose of the community service is to provide reference management training for postgraduate of State Islamic Institute of Samarinda. The training method used is direct practice in the classroom using three reference management software, namely Endnote, Mendeley, and Zotero. This activity was attended by 16 postgraduate students and they followed with great enthusiasm. After the training, the knowledge and abilities of postgraduate students experienced a significant increase and were committed to using the software in writing scientific papers.